STOCK PRICE AND PERFORMANCE OF INDONESIAN BANKING, CASE STUDY FOR THE PERIOD OF 2013-2016 - Cornelius Candra Adi Wibowo; Agus Sukoco; Ani Wulandari; Bukhuth Augendra (Journal of International Conference Proceedings (JICP), 2018)
The purposeof this study to analyze the effect of Return On Assets, Return On Equity and Earning Per Share to stock prices of Banking Companies listed in Indonesia Stock Exchange (IDX) period 2013-2016. This study analyzes the profitability ratios of financial statements of banking companies and their impact on stock prices. Method, The population of this research is Banking Companies listed in IDX period 2013-2016. Samples used as many as 10 companies Banking taken with purposive sampling technique that is the method of determining the sample based on certain criteria.The analytical technique used is Multiple Regression Analysis. Data is taken from the financial statements downloaded on the Indonesia Stock Exchange website and tested with SPSS 18 application. Result,Result of this study that the performance of Indonesian banking is influenced by Return On Asset (ROA), Return On Equity (ROE), has a significant influence on Stock Price, but Earning Per Share (EPS) has no significant effect on Stock Price The findingsof this study are banking companies that go public in Indonesia, their Stock Price is determined by the value of ROA and ROE and this will help provide useful information to other researchers, investors and banking companies Keywords: ROA, ROE, EPS danstock returns